The handbook of environmental remediation : classic and modern techniques - Hussain, Chaudhery Mustansar (Royal Society of Chemistry, 2020)
This handbook brings altogether classical and emerging techniques for hazardous wastes, municipal solid wastes and contaminated water sites.